Primary PCI in Elderly STEMI Patients: Risk Assessment and Management - Samiullah; Hameed Ullah; Abdul Waris; Khan, Muhammad Niaz; Nazeef Ullah; Abid Ullah (Indus Journal of Bioscience Research, 2024)
Objective: To evaluate the impact of frailty on clinical and procedural outcomes in elderly STEMI patients undergoing primary percutaneous coronary intervention (PCI) at Hayatabad Medical Complex, Peshawar. Methodology: A retrospective study was conducted from April 2023 to March 2024, including 300 patients aged ≥65 years divided equally into frail and non-frail groups (n=150 each). Data were collected on demographic characteristics, procedural outcomes, and complications. Statistical analysis included chi-square tests for categorical variables and t-tests for continuous variables, with a significance level of p<0.05. Results: The mean Killip class was significantly higher in frail patients (2.5 ± 0.8) compared to non-frail patients (1.8 ± 0.5; p<0.05). Symptom onset-to-treatment time was longer among frail patients (7.4 ± 2.1 hours vs. 5.8 ± 1.9 hours; p<0.05). TIMI grade 3 flow was achieved in 82% of non-frail patients compared to 65% in frail patients (p<0.05). Major adverse cardiac events (MACE) occurred in 42% of frail patients versus 18% of non-frail patients (p<0.05). ST-segment resolution was achieved in 78% of non-frail patients compared to 54% in frail patients (p<0.05). Conclusion: Frailty significantly impacts clinical and procedural outcomes in elderly STEMI patients, highlighting the need for tailored approaches to improve treatment and post-PCI care. Future studies should validate these findings in broader populations and explore advanced strategies to address frailty.